INTEGRATING TECHNOLOGY INTO PRIMARY ENGLISH LANGUAGE TEACHING: A CASE STUDY FROM UZBEKISTAN (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This study explores the integration of digital tools in teaching English to young learners in Uzbekistan. The research focuses on how technological devices such as tablets, smartboards, and language learning apps impact vocabulary acquisition and student motivation in primary classrooms. A mixed-methods approach was applied, including pre- and post-tests, classroom observations, and interviews with teachers. The findings reveal that technology-enhanced lessons increase student engagement and vocabulary retention. The article provides recommendations for effectively using digital tools in early language education.